Perceived Barriers of Tuberculosis Case Notification among Private Practitioners in Central Karnataka - Satish Ghatage; Anurupa MS; Swathi Aithal (Medsci Publications, 2021)
Background: India is the highest tuberculosis (TB) burden country in the world accounting for almost one-fourth of the global cases and deaths as per the global TB report 2021. There are evidences suggesting that private practitioners (PPs) in India are not equipped with sufficient knowledge to carry out proper management of TB patients and certain barriers in TB case notification. So the present study is under taken to explore the perceived barriers for TB case notification from private practitioners. Methodology: In-depth interview, qualitative research was done with the PPs who diagnosed and treated TB patients in 2018 but not notified to district TB centre. PPs were selected for in-depth interview by simple random sampling method. In-depth interview were stopped based on the saturation of data. Study was conducted from July-December 2018. Results: In-depth interview were conducted with 28 private practitioners. Perceived barriers for notification of TB cases by private practitioners were few misconceptions, patient's confidentiality and stigma, lack of co-ordination between public and private sector and lack of simplified mechanism for TB notification. Conclusion: Private practitioners are the main stake holders in moving the country toward TB elimination so addressing their challenges is the need of the hour. Trust building and reorientation of private practitioners will address the major misconceptions about the TB case notification.